2021
DOI: 10.1136/bmjspcare-2021-003258
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in hospitalised older patients: the WHALES short-term predictive score

Abstract: ObjectiveTo develop and validate the WHALES screening tool predicting short-term mortality (3 months) in older patients hospitalised in an acute geriatric unit.MethodsOlder patients transferred to an acute geriatric ward from June 2017 to December 2018 were included. The cohort was divided into two groups: derivation (n=664) and validation (n=332) cohorts. Cause for admission in emergency room, hospitalisation history within the previous year, ongoing medical conditions, cognitive impairment, frailty status, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(38 reference statements)
0
4
0
Order By: Relevance
“… 14 , 31 A discharge diagnosis of pneumonia and a self-reported feeling of physical fatigue have also previously been shown to be independent prognostic factors of death in older patients. 13 , 33 , 49 Previous studies also found a correlation between mortality and routine laboratory tests from hospitalization, such as C-reactive protein, creatinine, sodium, hemoglobin, and glucose. 15 , 50–52 We have not been able to find studies that have examined eGFR, bilirubin, or alkaline phosphatase as prognostic factors of mortality, though these were all high-ranking variables in our model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 14 , 31 A discharge diagnosis of pneumonia and a self-reported feeling of physical fatigue have also previously been shown to be independent prognostic factors of death in older patients. 13 , 33 , 49 Previous studies also found a correlation between mortality and routine laboratory tests from hospitalization, such as C-reactive protein, creatinine, sodium, hemoglobin, and glucose. 15 , 50–52 We have not been able to find studies that have examined eGFR, bilirubin, or alkaline phosphatase as prognostic factors of mortality, though these were all high-ranking variables in our model.…”
Section: Discussionmentioning
confidence: 94%
“…The level 4 model achieved good discrimination (AUROC 0.860) and was comparable to other models that predict mortality in older patients, though we have not been able to find other models that focus on early discharge. [30][31][32][33] However, besides improving predictive performance, introducing comorbidities and number of prescription medications (level 4) makes the model more labor-intensive for the physician, as this information would often require the manual tallying of the patient's comorbidities and medications. The level 5 model performed comparably to the level 4 model, but with slightly higher specificity and lower sensitivity.…”
Section: Dovepressmentioning
confidence: 99%
“…The Hosmer-Lemeshow goodness-of-t test was used to assess the calibration of the constructed predictive models. If the obtained statistic is smaller, the corresponding P value is larger, which means that the calibration degree of the prediction model is higher, the prediction value and the actual observation value have better consistency, and the tting effect of the model is better [41][42] .…”
Section: Model Evaluationmentioning
confidence: 99%
“…Nowadays, thirty percent of hospital admissions for any cause belong to people 65 years and older. This takes relevancy since older patients have more prevalence of frailty, comorbidity, polypharmacy, and other geriatrics syndromes that worsen functional and mortality prognosis, have longer hospital length stays and increased admissions to the intensive care unit (3). According to Steinmeier and collaborators, intrahospital mortality can reach 17.1%, meanwhile this percentage increases to 33.7% in the intensive care unit (4).…”
Section: Introductionmentioning
confidence: 99%